ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017 – 2021) - Putri Sinta Syarif Syarif; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2023)
This research is motivated by the importance of dividend policy for investors in making investment decisions. In addition, there are differences in approach in previous studies regarding the factors that influence dividend policy in manufacturing companies. This study aims to identify the factors that influence the dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2021. The factors examined include liquidity, leverage, profitability, collateralizable assets, and growth in net assets. This study uses agency theory to generate testable hypotheses. Testing these hypotheses is expected to provide empirical findings.            This study uses secondary data from 195 manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The purposive sampling method is applied in this study, and the sample chosen includes 44 manufacturing companies. Furthermore, the analysis method used in this study is multiple linear regression.            The results of this study indicate that leverage and growth in net assets have a significant negative influence on dividend policy. Meanwhile, profitability and collateralizable assets have a significant positive influence on dividend policy. On the other hand, liquidity shows a positive but insignificant influence on the dividend policy.